The National Committee on Biosafety of the Philippines (NCBP) Thirty Years of Biosafety Regulations in the Philippines - Mendoza, Evelyn Mae Tecson; Garcia, Roberta N.; Mendoza, Trina Leah T.; Baurile, Ladylove May B.
"The book 'Thirty Years of Biosafety Regulation in the Philippines' aims to present experiences of various stakeholders in the implementation of the biosafety regulatory system in the country. Partocularly, the book provides an overview on how the different Competent National Authorities (CNAs) carried out its mandate in the implementation of the National Biosafety Framework (NBF) and the country's compliance to its International Obligations as a party to the Cartagena Protocol on Biosafety (CPB). This book likewise narrates how and why new biosafety policies and guidelines such as the DOST-DA-DENR-DOH-DILG Joint Department Circular No.1 and the NCBP Resolution on the regulationof Plant Breeeding Innovations (PBIs) or New Plant Breeding Techniques (NBTs) were issued.